Methods And Principles Of Language Teaching In Modern Education - Lazizhon Abdullahanovich Babahanov (Euro Asian Journal Publishing, 2024)
The article examines modern methods and principles of language learning in the context of modern education. Key approaches, including the communicative method, the project-oriented approach, the use of digital technologies, and contextual learning, are analyzed. Particular attention is paid to the principles of communication, individualization, cultural awareness, consistency, and variability, which contribute to the effectiveness of language learning. The role of the teacher as a mentor, who organizes the educational process taking into account modern requirements, is emphasized. The article presents recommendations for implementing innovative methods aimed at developing students' linguistic and intercultural competencies. The conclusion is drawn about the importance of integrating new technologies and methods to improve the quality of language education and the professional training of teachers
Keywords: methodology; language learning; modern approaches